2009
DOI: 10.1016/j.ejcts.2009.06.033
|View full text |Cite
|
Sign up to set email alerts
|

The myocardial protective effect of adenosine as an adjunct to intermittent blood cardioplegia during open heart surgery

Abstract: Compared with simple cold blood cardioplegia in heart valve replacement patients, ADO pretreatment as an adjunct to 1 mmol l(-1) ADO cold blood cardioplegia may reduce cTnI, IL-6 and IL-8 release, resulting in reduced myocardial injury in ultrastructure after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
1
20
0
2
Order By: Relevance
“…This study showed that adenosine infusion (250-350 mg kg À1 Â 10 min) just prior to cardiopulmonary bypass (CPB) resulted in immediate improvements in post-bypass cardiac index (CI) in the operation room and improved postoperative ventricular performance, lowered postoperative myocardial energy demand, and decreased myocellular injury. Similar results are reported by Wei et al [9], who pretreated patients with adenosine (total, 650 mg kg À1 via central vein infusion) before initiating CPB, and Liu et al [10], who infused adenosine (100 mg kg À1 min À1 Â 10 min) before aortic crossclamping and delivering antegrade cold-blood cardioplegia solution in patients undergoing valvular operations. Administering adenosine directly into the aortic root immediately after aortic cross-clamping and just before initiating cardioplegia can also optimize the myocardial protective effect of conventional cardioplegia and offer better postoperative myocardial performance after CPB [11,12].…”
Section: Introductionsupporting
confidence: 75%
“…This study showed that adenosine infusion (250-350 mg kg À1 Â 10 min) just prior to cardiopulmonary bypass (CPB) resulted in immediate improvements in post-bypass cardiac index (CI) in the operation room and improved postoperative ventricular performance, lowered postoperative myocardial energy demand, and decreased myocellular injury. Similar results are reported by Wei et al [9], who pretreated patients with adenosine (total, 650 mg kg À1 via central vein infusion) before initiating CPB, and Liu et al [10], who infused adenosine (100 mg kg À1 min À1 Â 10 min) before aortic crossclamping and delivering antegrade cold-blood cardioplegia solution in patients undergoing valvular operations. Administering adenosine directly into the aortic root immediately after aortic cross-clamping and just before initiating cardioplegia can also optimize the myocardial protective effect of conventional cardioplegia and offer better postoperative myocardial performance after CPB [11,12].…”
Section: Introductionsupporting
confidence: 75%
“…This was achieved using a concentration of Iso (200 nM) significantly higher than the concentration of isoproterenol in blood plasma used clinically (0.02-0.2 μg/kg/min; equivalent to about 1.3-13 nM) [6]. In contrast, the concentration of adenosine used in our experiments (30 μM) is considerably lower than that used for blood cardioplegia during cardiac surgery (1–2 mM) [7,8]. Therefore it is important to test both drugs at concentrations that are clinically relevant.…”
Section: Introductionmentioning
confidence: 84%
“…While patients are on the CPB machine, pro-inflammatory cytokines such as tumor necrosis factor alpha (TNF-α) and interleukins (IL) 1, 6 and 8 are released and mediate the systemic inflammatory response syndrome (SIRS), which is believed to play an essential role in myocardial ischemia and reperfusion injury [43]. Table 2 describes some of these and other markers.…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine could be used in ischemic preconditioning (IPC) as an adjunct to cross-clamping the aorta. Compared with simple cold blood cardioplegia in heart valve replacement patients, adenosine pretreatment (100 μg/kg/min, 10 min) as an adjunct to 1 mM adenosine cold blood cardioplegia may reduce CTnI, IL-6, and IL-8 release, resulting in reduced myocardial injury after surgery [43]. The leakage of these cytokines causes post-op myocardial dysfunction and damage.…”
Section: Introductionmentioning
confidence: 99%